TheMC4R(I251L) Allele Is Associated with Better Metabolic Status and More Weight Loss after Gastric Bypass Surgery - Uyenlinh L. Mirshahi; Christopher D. Still; Kathryn Masker; Glenn S. Gerhard; David J. Carey; Tooraj Mirshahi (2011)
Factors that influence long-term weight loss after Roux-en Y gastric bypass (RYGB) surgeries are poorly defined. The melanocortin system plays an important role in regulating energy homeostasis, satiety, and glucose metabolism. Variations of the MC4R comprise the most prevalent monogenetic obesity disorder.The objective of the study was to examine the role of MC4R variants and diabetic status in long-term weight loss after RYGB.In 1433 extremely obese patients who underwent RYGB, we sequenced for genetic variants of MC4R. We examined the MC4R genotype and its relationship with weight loss profile, and clinical phenotypes accumulated during a 48-month period before and after surgery.We found 80 subjects with rare and common variants of MC4R in the RYGB cohort. Among these, 26 and 36 patients carry the I251L and V103I variants, respectively. These common alleles are negatively associated with obesity. Remarkably, after the 12-month presurgery caloric restriction and RYGB, I251L allele carriers lost 9% more weight (∼9 kg) compared with the noncarriers, continued rapid weight loss longer, regained less weight, and had lower presurgery homeostatic model assessment for insulin resistance values. Normoglycemic, I251L allele carriers lost more weight compared with their diabetic and prediabetic counterparts and maintained their weight loss. Among noncarriers, normoglycemic individuals initially lost more weight compared with dysglycemics, but this difference was not maintained in the long term.Individuals carrying the I251L common allele are predisposed to better clinical outcome, reduced risk of type 2 diabetes, and better weight loss during diet and surgical interventions. Diabetic status has only a small, short-term effect on weight loss after RYGB.